Serum Zinc Level and Urinary Zinc Excretion in Liver Cirrhotic Patient - Catharina Triwikatmani; Putut Bayupurnama; Sutanto Maduseno; Neneng Ratnasari; Fahmi Indrarti; Siti Nurdjanah (The Indonesian Society for Digestive Endoscopy, 2009)
Background: Zinc deficiency is commonly found in liver cirrhotic patient, and it is usually caused by excessive urinary excretion that is exaggerated by diuretic agents. The objective of this study is to know the differences of zinc serum concentration according to the Child-Turcotte-Pugh (CTP) score and clinical factors that influence zinc serum level and 24-hour urinary zinc excretion. Method: The design of this study was cross-sectional. In adult patients with liver cirrhosis, blood samples were collected after patients had fasted for at least 8 hours. Zinc levels were measured by the flame atomic absorption spectrophotometry method. Correlation test was performed among numeric variables, as well as Mann-Whitney U test to measure mean differences of zinc serum concentration and of 24-hours urinary zinc excretion according to clinical factors. The level of significance was p 0.05. Results: During the period of May 1st - September 30th 2007, there were 36 eligible patients. The mean value of zinc serum levels was 63.70 ± 24.85 µg/dL. There were 24 (66.67%) patients with hypozincemia. The mean value of 24-hour-urinary zinc excretion was 787.52 ± 570.20 µg. There were 19 (52.8%) patients with urinary zinc excretion 550 µg/24 hour. The results of mean difference test of zinc serum concentration between CTP score B and C showed no statistical significance (p = 0.052). Urinary zinc excretion correlated to urine volume (r = 0.638, p = 0.000), and it was higher in hospitalized patients compared to outpatients. It also was higher in men compared to women. There were no statistically significant differences in zinc serum level, zinc urinary level, and urinary zinc excretion on the administration of diuretic agents. Conclusion: There were no significant differences of fasting zinc serum concentration in cirrhotic patients between the CTP scores B and C. In liver cirrhotic patients, urinary zinc excretion positively correlates to urine volume. Keywords: liver cirrhosis, serum zinc level, urinary zinc excretion